2018
DOI: 10.1002/cncr.31286
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and mutational spectrum of highly differentiated, paired box 3:forkhead box protein o1 fusion–negative rhabdomyosarcoma: A report from the Children's Oncology Group

Abstract: Interestingly, Hh and mTOR gene mutations were previously associated with rhabdomyomas, which are also known to preferentially arise at head/neck and genitourinary sites. Findings from this study further support the idea that PF-, highly differentiated RMS tumors and rhabdomyomas may represent a continuous spectrum of tumors. Cancer 2018;124:1973-81. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Previous publications reported PTCH1‐inactivating mutations (resulting in hedgehog (Hh)‐signaling pathway activation) or a deregulation of the Hh‐signaling pathway in RMS tumors with high levels of myogenic differentiation . As previously suggested by others, highly differentiated RMS tumors and rhabdomyomas might form a continuous spectrum of tumors. Notably, no infant had nevoid basal cell carcinoma syndrome (or Gorlin syndrome), characterized by a PTCH1 inactivating mutation .…”
Section: Discussionmentioning
confidence: 84%
“…Previous publications reported PTCH1‐inactivating mutations (resulting in hedgehog (Hh)‐signaling pathway activation) or a deregulation of the Hh‐signaling pathway in RMS tumors with high levels of myogenic differentiation . As previously suggested by others, highly differentiated RMS tumors and rhabdomyomas might form a continuous spectrum of tumors. Notably, no infant had nevoid basal cell carcinoma syndrome (or Gorlin syndrome), characterized by a PTCH1 inactivating mutation .…”
Section: Discussionmentioning
confidence: 84%
“…Due to their rarity, the molecular characteristics of benign lesions have been poorly explored. Evidence of Hedgehog pathway mutations in a subset of highly differentiated RMS and fetal rhabdomyomas 42 together with rare evidence of malignant transformation 43 might suggest that RMS and rhabdomyomas may exist on a continuum. The identification of ZEB2 deletions in one rhabdomyoma adds an additional genetic alteration that may be involved in this spectrum of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the progress made with genomic characterization of PAX ‐fusion–positive and PAX ‐fusion–negative RMS, many important biological questions remain, including: PAX ‐fusion–positive RMS tumors show a higher propensity to metastasize compared with PAX ‐fusion–negative tumors, and loss of TP53 increases the invasive potential of PAX ‐fusion–negative RMS tumors in a zebrafish model, but what are the mechanisms that govern invasion and metastasis in PAX ‐fusion–positive and –negative RMS? The YAP/TAZ, RAS/RAF/MEK/ERK, PI3 kinase/mTOR, MYOD/MYF5, Notch, WNT, Hedgehog, and EZH2 pathways have been implicated in PAX ‐fusion–negative RMS as blocking muscle differentiation; can this knowledge be leveraged diagnostically or therapeutically? Animal modeling studies have shown that PAX ‐fusion–negative RMS can be initiated from myogenic and nonmyogenic (endothelial) precursors, while differentiating fetal myoblasts are most poised to develop PAX ‐fusion–positive RMS . Because the RMS cell of origin influences not only histological identity but also site of disease and response to therapy, what are the RMS cell(s) of origin in human disease? What is the role of immune and other cells in the tumor microenvironment in driving RMS progression, metastasis, and therapy resistance? What are the risk factors and germline mutations associated with an increased risk of RMS development? What are the most predictive preclinical models for RMS and can these be exploited for rapid and better prioritization of preclinical therapy testing? How can we best leverage new technologies, such as CRISPR‐Cas9 screening of protein domains, to identify new drug targets for RMS? What are the mechanisms by which MYOD1 L122R drives spindle cell/sclerosing RMS tumorigenesis? …”
Section: Critical Biological Problemsmentioning
confidence: 99%
“…The YAP/TAZ, RAS/RAF/MEK/ERK, PI3 kinase/mTOR, MYOD/MYF5, Notch, WNT, Hedgehog, and EZH2 pathways have been implicated in PAX ‐fusion–negative RMS as blocking muscle differentiation; can this knowledge be leveraged diagnostically or therapeutically?…”
Section: Critical Biological Problemsmentioning
confidence: 99%